PENTINGNYA KOMPETENSI SUMBER DAYA MANUSIA DAN PENERAPAN APLIKASI SISKEUDES DALAM PENGELOLAAN KEUANGAN DESA (Studi Kasus Pada Kecamatan Lantari Jaya Kabupaten Bombana) - Asmawati, Asmawati; Rahim, Manat; Husin, Husin (Pascasarjana Universitas Halu Oleo, 2021)
This research aims to test and analyze the importance of human resource competence and the application of siskeudes application in village financial management in Lantari Jaya district of Bombana Regency. Respondents in this study were all apparatus villages that are directly involved in the financial management of the village, which numbered 99 people consisting of the Village Head as technical executor of village financial management (PTPKD), the implementer of village financial management (PPKD) consisting of the Village Secretary, Kaur/Section, and the Village Consultative Agency (BPD) which consists of 5 people, in 9 villages in Lantari Jaya Sub-district. The data analysis used in this study is a WarpPLS analysis technique. The results showed that (1) the competence of the village apparatus had a significant effect on the financial management of the village (2) the application of siskeudes application had a significant effect on the financial management of the village.Â Keywords: Human Resource Competence, Siskeudes Application, Village Financial ManagementÂ